Hypoxia at the heart of sudden infant death syndrome? - Neary, Marianne T. (2013)
Sudden infant death syndrome (SIDS) remains a significant clinical problem without an accepted pathological mechanism, but with multiple conflicting models. Mutation in a growing number of genes has been found post mortem in SIDS cases, notably genes encoding ion channels. This can only account for a minority of cases, however. Our recent work on a novel mouse model of SIDS suggests a potentially more widespread role for cardiac arrhythmia in SIDS without needing to invoke inheritance of abnormal ion channel genes. We propose a model for SIDS pathogenesis whereby postnatal hypoxia leads to delayed maturation of the cardiac conduction system and an increased risk of cardiac arrhythmia. Our model may integrate several epidemiological findings related to risks factors for SIDS, and agrees with previous work suggesting a common final pathological pathway in SIDS.